Interpretasi Perubahan Penduduk Indonesia Dengan Menggunakan Beberapa Peta AGIHAN = The Interpretation of Indonesian Population Changes Using Some Distribution Maps - Km, Sudarsono (Majalah Geografi Indonesia, 1988)
Conducting a macro research on population which covers the entire territory of Indonesian and compiling the findings on maps appears to be an arduous procedure. In this respect, population distribution maps may save much time and funds. Although scarcely available, population distribution maps may yet be taken into consideration if it concerns geographical population studies. Comparison and interpretation of phenomena such as population changes in every province may already reveal distribution patterns and interrelated factors. The shortcomings of the used distribution maps for this article are complemented by secondary data.